Sprint-specific training in youth: Backward running vs. forward running training on speed and power measures in adolescent male athletes - Uthoff, A.; Oliver, J.; Cronin, J.; Harrison, C.; Winwood, P. (The Journal of Strength and Conditioning Research, 2020)
This study compared the effects of 2 sprint-specific training programs against the natural development of speed, power, and stiffness in a group of adolescent male athletes. Forty-three male adolescents (aged 13-15 years) were randomly assigned to 1 of 2 training groups; backward running training (BRT = 26), or forward running training (FRT = 17). A physical education class (n = 24) of similar age constituted a control (CON) group. Both training groups performed running sessions matched for distance and intensity biweekly for 8 weeks. Parametric and magnitude-based inferences were used to analyze within group (pre-post measures) and between group (gain scores) for 10-m, 10- to 20-m, and 20-m sprint times, vertical countermovement jump (CMJ) height, and vertical leg stiffness. Both running groups significantly improved (p = 0.05) in all performance tests from pre-training to post-training, with effect sizes ranging from -1.25 to 0.63. When the groups were compared, the BRT and FRT groups improved significantly (p = 0.01) on all sprint performances and stiffness relative to the CON group. The BRT group demonstrated favorable effects for 10-m and 20-m sprint performances (effect size [ES] = -0.47 and -0.26, respectively) and CMJ height (ES = 0.51) compared with the FRT group. These results demonstrate that forward and backward sprint-specific training programs enhance speed and power measures more than natural development in adolescent male athletes. Furthermore, the greater training responses in sprint performance and CMJ ability indicate that BRT is a useful tool for improving concentric strength and power and may be classified as a sprint-specific training method.